The Influence of Internal Locus of Control, Collective Efficacy, and Digital Marketing Ability on Business Success in Women Agricultural Product Processors (Jurnal Sosial Ekonomi Pertanian, 2026)
AbstractThis study aims to analyze the influence of internal locus of control, collective efficacy, and digital marketing capability on business success among women agricultural processors in Kota Sigli Subdistrict, Pidie Regency. The population of this study was all women agricultural processors running micro-enterprises in the location. Sample selection was conducted using the purposive sampling technique based on the following criteria: (1) women who process agricultural products, (2) run micro-enterprises for at least 1 year, and (3) are members of Women Farmers Groups (Kelompok Wanita Tani/KWT). The sample size of 115 respondents was determined based on the Hair et al. (2019) formula with an approach of 5–10 times the number of indicators. The analytical method employed was Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with two stages of evaluation, namely the measurement model evaluation (outer model) through validity and reliability tests, and the structural model evaluation (inner model) through R-Square test, F-test, and t-statistic test to examine the significance of relationships among variables. The hypothesis testing results showed that internal locus of control had a significant effect on business success (t-statistic = 2.722; p-value = 0.007), while collective efficacy (t-statistic = 0.118; p-value = 0.906) and digital marketing capability (t-statistic = 1.643; p-value = 0.100) had no significant effect. The R-Square value of 0.453 indicates that the three independent variables simultaneously influence business success by 45.3%, with the remaining percentage influenced by other variables outside the model. These findings suggest that individual psychological factors determine business success more than collective factors or digital capabilities, implying that women's empowerment programs should place greater emphasis on strengthening personal capacity, accompanied by institutional support and digital transformation that is responsive to structural barriers and patriarchal cultural values in Aceh.Keywords:  Internal Locus of Control; Collective Efficacy; Digital Marketing; Business Success; Women Agricultural Processors